The Development of Electronic Student Worksheets (E-LKPD) Based on Project-Based Learning in IPAS (Integrated Science and Social Studies) Learning for Grade V at SDN 03 Koto Baru - Putri, Dahara Atika; Hader, Antik Estika; Patmaneli, Patmaneli (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to develop an electronic student worksheet (E-LKPD) based on project-based learning for IPAS (Integrated Science and Social Studies) learning in grade V at SDN 03 Koto Baru. This research uses the Research and Development (R&D) method with the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation. The study was conducted at SDN 03 Koto Baru during the 2025 academic year, with the research subjects being 27 grade V students. Data collection techniques were carried out through student and teacher response questionnaires, as well as validation sheets involving media experts, content experts, and language experts. The results of this study indicate that the developed E-LKPD is a valid learning media. This can be seen from the graphic expert validation score of 89%, categorized as very valid. The language expert validation scored 76%, categorized as valid. The content expert validation scored 82%, categorized as very valid. The module expert validation scored 75%, categorized as valid. The question expert validation scored 75%, categorized as valid. This means that the learning media is suitable for use by both teachers and students. The practicality results from the teacher’s evaluation showed a score of 90%, categorized as very valid, and the grade V students scored 89%, also categorized as very valid. In conclusion, the project-based learning E-LKPD for IPAS learning in grade V at SDN 03 Koto Baru, developed by the researcher, is suitable for use, as it meets the criteria of being valid, practical, and effective.